Gagasan Dasar dan Pemikiran Multikulturalisme - Ramedlon Ramedlon; Idi Warsah; Al-Fauzan Amin; Adisel Adisel; Suparno Suparno (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
ABSTRACT This study aims to determine the ideas and thoughts of multiculturalism. The method used in this study uses the library method. The result of this research is that the concept of multiculturalism has three components. The first is related to culture; Second, this concept is related to cultural pluralism; And third, the concept includes specific ways of dealing with this diversity. Therefore, multiculturalism is not a practical political doctrine, but a perspective or a kind of idealism in human life. The conclusions of the research show that multiculturalism corrects the weaknesses of the idea of ​​fusion, including: (1) Dividing the cultural movement into two parts, namely: Opening up space for all ethnic groups to express themselves in the same cultural order and private spaces used by every free ethnic group. to express their culture. (2). Fostering national and state pride. (3) Respect and respect civil rights, including the rights of minorities. Keywords: Ideas, Multiculturalism, Thought